Fiscal Decentralization to Rural Local Governments in India : A Case Study of West Bengal State - Bahl, R.; Sethi, G.; Wallace, S. (2012)
Rural local governments in India provide essential services to over 70 percent of the national population. Yet, little is known about the efficacy of the financing system that supports these local governments, nor is there a fiscal information system that will allow a tracking of rural local government expenditures and revenues. In this article, we describe the role of rural local governments in India's; federal system, and use a database, newly gathered for West Bengal State, to present an analysis of rural local government financing patterns. We find that expenditures are significantly higher in less populated and more backward gram panchayats. At the margin, however, higher rates of literacy also are associated with higher levels of spending, suggesting an education effect.